Phosphorylation of Argonaute proteins affects mRNA binding and is essential for microRNA‐guided gene silencing in vivo. (23rd June 2017) - Quévillon Huberdeau, Miguel; Zeitler, Daniela M; Hauptmann, Judith; Bruckmann, Astrid; Fressigné, Lucile; Danner, Johannes; Piquet, Sandra; Strieder, Nicholas; Engelmann, Julia C; Jannot, Guillaume; Deutzmann, Rainer; Simard, Martin J; et al.
Abstract: Argonaute proteins associate with microRNAs and are key components of gene silencing pathways. With such a pivotal role, these proteins represent ideal targets for regulatory post‐translational modifications. Using quantitative mass spectrometry, we find that a C‐terminal serine/threonine cluster is phosphorylated at five different residues in human and Caenorhabditis elegans . In human, hyper‐phosphorylation does not affect microRNA binding, localization, or cleavage activity of Ago2. However, mRNA binding is strongly affected. Strikingly, on Ago2 mutants that cannot bind microRNAs or mRNAs, the cluster remains unphosphorylated indicating a role at late stages of gene silencing. In C. elegans, the phosphorylation of the conserved cluster of ALG‐1 is essential for microRNA function in vivo . Furthermore, a single point mutation within the cluster is sufficient to phenocopy the loss of its complete phosphorylation. Interestingly, this mutant retains its capacity to produce and bind microRNAs and represses expression when artificially tethered to an mRNA. Altogether, our data suggest that the phosphorylation state of the serine/threonine cluster is important for Argonaute–mRNA interactions. Synopsis: A conserved phosphorylation site in Argonaute 2, a key effector of miRNA‐dependent gene regulation, controls mRNA binding in human and worms, revealing that the activity of the RNAi machinery is dynamically regulated. Mapping of post‐translational modifications on endogenous Argonaute proteins across species reveal highly conserved phosphorylation events. A conserved phosphorylation cluster on the PIWI domain of Argonaute ALG‐1 is essential for microRNA‐guided gene regulation in Caenorhabditis elegans . Ago2 mutants mimicking hyper‐phosphorylation of the cluster bind miRNAs and are catalytically active. Hyper‐phosphorylation of the cluster on human Ago2 alters miRNA target binding. Abstract : The discovery of a conserved phosphorylation site in Argonaute 2, a key effector of miRNA‐dependent gene regulation, reveals a new level of active control in the RNA silencing machinery.